IMPLEMENTATION OF R.A. 9003 (ECOLOGICAL SOLID WASTE MANAGEMENT ACT) IN BARANGAY GEN. T. DE LEON, VALENZUELA CITY: AN ASSESSMENT - Andaya, Eduardo; Antonio, Myla; Espina, Myla; Ignacio, Juditha Roanne; Rebuya, Mark Angelo; John A. Cabaddu (Journal of Governance and Public Administration, 2025)
This study evaluated the implementation of Republic Act 9003 (R.A. 9003), also known as the Ecological Solid Waste Management Act, in Barangay Gen. T. de Leon, Valenzuela City, Philippines. The researchers used a mixed-methods approach, combining surveys and interviews to collect both quantitative and qualitative data. Surveys were conducted with 398 residents aged 17 to 65, and interviews were held with five residents and two members of the Barangay Solid Waste Management Committee. This study aimed to evaluate the effectiveness of the Solid Waste Management Program in the barangay, with a focus on waste segregation, recycling, garbage collection, implementation, and public awareness. The study also aimed to understand residents' views and reactions to the program and its impact on effective governance in the barangay. Findings revealed that while residents demonstrated awareness of the program and engaged in activities such as waste segregation and recycling, there were areas that needed improvement. Waste collection was generally rated as very effective; however, there was a recognized need for enhanced information dissemination, especially regarding waste reduction and recycling. The study concluded that cooperation between barangay committees and citizens is vital for the success and sustainability of solid waste management programs. It also emphasized the government's responsibility in addressing health issues related to waste, such as dengue and cholera. Recommendations included the need for continuous information campaigns, the implementation of policies with penalties for non-compliance, and the establishment of Material Recovery Facilities in each barangay.   Keywords : Solid Waste Management, RA 9003, Implementation, Public Awareness